Cultivating Gender Equality to Achieve Educational and Social Sustainability among Indigenous Women of Malaysia - Karim, Rafidah Abd; Mustapha, Ramlee (European Scientific Journal, ESJ, 2025)
The ultimate aim of sustainability is to meet present-day requirements without endangering those of future generations. Gender equality is essential for social and educational sustainability because it allows people and society to reach their full potential, which produces more inclusive, equitable, and profitable results. This study depicts certain cases of the indigenous women in Malaysia, exploring the gender equality aspects in achieving educational and social sustainability in the indigenous peoples. A qualitative case study approach was employed for this case study. A semi-structured interview was conducted with 10 indigenous women from two main tribes, which are the Mah Meri and Temiar. Data were transcribed and analysed using a thematic analysis process. The findings reveal that there were three major themes generated from the thematic analysis, which are contributions to society and freedom in the pursuit of education. This case study highlights that indigenous women play a vital role in creating a balance between the responsibilities of the genders in order to achieve SDG5 (gender equality) and educational sustainability in indigenous communities.